Family communication as... exploring metaphors for family communication - Manning, Jimmie; Allen, Jordan; Denker, Katherine J. (John Wiley & Sons, 2022)
Before the last half of the twentieth century, the phrase "family communication as relationship" would have struck a reader as unintelligible. Communication between and among family members was neither an object of scientific study nor a focus of individual reflection or cultural analysis. Moreover, according to the Online Etymology Dictionary, the word relationship first appeared in 1744 but was not applied "specifically of romantic or sexual relationships" for another two hundred years. The field of communication made a turn to studying communication in relationships and the family during the late 1960s and 1970s as it abandoned the common but fairly bloodless definition of interpersonal communication as face-to-face communication between two people. Influenced by classic works in family systems theory, such as that by Satir (1972), Watzlawick, Beavin, and Jackson (1967), and Bateson (1972), the field adopted the metaphor of the family as a system of relationships built, maintained, changed, and destabilized through interaction. Within ten years, Galvin and Brommel (1982) had produced a textbook on family communication that could overview the extensive research analyzing patterns of interaction within families. Starting with couple interaction data (Gottman 1979), Gottman (2002) built a strong mathematical model for the metaphors of family interaction presented in the family system theories. Even though the metaphor of family communication as relationship has generated important research directions, some theorists argue that metaphors are imprecise, ambiguous, and therefore have no place in scientific discourse. But language, even much scientific language, is metaphorical because we discuss one thing in terms of another (Lakoff and Johnson 1980). Of course, literal statements (e.g., the cat sits on the mat) are possible but as soon as we move from concrete physical experience to talk about abstractions, we employ metaphor."--Provided by publisher.